Analisis Yuridis Perlindungan Hukum Atas Tanah Bersertifikat yang Tumpang Tindih dengan Tanah Negara - Dharma Wira Wijaya; Tanudjaja . (CV. ITTC INDONESIA, 2026)
This research examines the legal issues concerning the legal position of certified freehold land that is subsequently proven to overlap with state land, as well as the legal protection for certificate holders who have complied with correct legal procedures. This issue is significant given the increasing number of overlapping cases causing legal uncertainty and public losses. This research employs a normative juridical method with statutory, conceptual, and case study approaches. The findings indicate that the legal position of certified freehold land overlapping with state land is weak as it contains fundamental substantive defects contradicting Article 2 paragraph (1) of the Basic Agrarian Law (UUPA). Based on Article 32 of Government Regulation No. 24 of 1997, the evidentiary power of certificates is strong but not absolute, thus revocable if physical or juridical data is incorrect. Legal protection for good faith certificate holders can be provided through preventive and repressive mechanisms, including priority rights, compensation rights, and rights to obtain other rights. This research recommends harmonization of legislation, strengthening the land registration system, establishing a clear compensation mechanism, and firm eradication of land mafia.